2015
DOI: 10.1016/j.beproc.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Food neophobia in wild and laboratory rats (multi-strain comparison)

Abstract: Although empirical studies comparing neophobia in wild and laboratory rats have been conducted in the past, a few decades have passed since most of them were completed. This is a substantial period of time in the case of fast-breeding animals such as rats. Equally important are the inconsistencies in research findings with respect to comparisons between wild and laboratory rats, and within domesticated strains. As well as having the aim of updating knowledge of neophobia among different types of rats, the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 43 publications
(67 reference statements)
3
45
1
3
Order By: Relevance
“…Interestingly, rats that were fed the control diet also exhibited a significant increase compared with rats fed the regular diet, suggesting that at least a portion of the increased body mass exhibited by the HFD group could be attributed to the novelty of the diet, as the consumption of a novel diet has been shown to induce weight gain after an initial (1 d) period of neophobia (Eckel and Ossenkopp, 1993; Modlinska et al, 2015). Taking this factor into account, the HFD group gained 1% body weight above that of the control diet group.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, rats that were fed the control diet also exhibited a significant increase compared with rats fed the regular diet, suggesting that at least a portion of the increased body mass exhibited by the HFD group could be attributed to the novelty of the diet, as the consumption of a novel diet has been shown to induce weight gain after an initial (1 d) period of neophobia (Eckel and Ossenkopp, 1993; Modlinska et al, 2015). Taking this factor into account, the HFD group gained 1% body weight above that of the control diet group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SSD groups demonstrated low resistance to the new food. Modlinska et al [72] also showed that rats did not avoid eating unfamiliar foods, displaying only a temporary reduction in the amount of the new food consumed. In fact, both SSD groups in the present study ingested a greater amount of palatable diet in the first exposure (PN150), rendering unlikely the possibility of neophobia regarding the diets used here.…”
Section: Effects Of Early Exposure To Nicotine On the Food Preferencementioning
confidence: 94%
“…This increase was observed in cells that were not TH‐positive, although it occurred regardless of whether the rat consumed the SCM. It is difficult to interpret this observation, although it may point to a role for the SuMM in learning and/or the physiological response in food neophobia …”
Section: Discussionmentioning
confidence: 99%